2018
DOI: 10.1136/jramc-2018-000920
|View full text |Cite
|
Sign up to set email alerts
|

Lost productivity among military personnel with cardiovascular disease

Abstract: CVDs are associated with significant lost productivity among military personnel. There is a statistically significant relation between some military occupation characteristics and lost productivity from CVD. Level of income, teamwork and physical activity have the greatest effects on lost productivity. Military workers who were suffering from other chronic conditions (in addition to CVD) were four times more likely to lose productivity. A supportive work environment should be created for military personnel wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Many aspects of military service, such as the primacy of mission success and training for that purpose, are generalizable. However, recruitment policies and differing health economies coupled with cultural and racial [131][132][133] variances may impact on background levels of cardiovascular disease (CVD). 134,135 As in the general population, age is an important determinant for CVD in the military, [124][125][126] with the incidence of death in the US military secondary to CAD for those <35 years of age being 0.65 per 100 000 service years, 13.69 in those >35 years of age, and 83.5 in those >50 years.…”
Section: Military Personnelmentioning
confidence: 99%
“…Many aspects of military service, such as the primacy of mission success and training for that purpose, are generalizable. However, recruitment policies and differing health economies coupled with cultural and racial [131][132][133] variances may impact on background levels of cardiovascular disease (CVD). 134,135 As in the general population, age is an important determinant for CVD in the military, [124][125][126] with the incidence of death in the US military secondary to CAD for those <35 years of age being 0.65 per 100 000 service years, 13.69 in those >35 years of age, and 83.5 in those >50 years.…”
Section: Military Personnelmentioning
confidence: 99%
“…These authors concluded that completing tasks in teams and performing tasks with peers for the first time had a more significant impact on success. In another study, Gharasi-Manshadi et al (2018) associated military productivity loss with cardiovascular disease and comorbidities. As the most influential factors of productivity loss, they included teamwork and physical activity level, as well as income level.…”
mentioning
confidence: 94%
“…Psychophysiological stressors are easily found, such as sleep and resources [5] (water and food) deprivation while deployed in combat, which leads to psychological, cognitive, and physical impairment; adverse weather conditions that lead to hypothermia or acute dehydration [6], and heights of over 3500 m, which lead to hypoxic conditions [7]; and periods of high physical and psychological demands during either training or during operative missions [8,9]. To a large extent, all these highly stressful demands require an optimal psychological level, and ultimately a high level of physical performance, muscular strength, and optimal cardiovascular health through their active duty to tolerate the multiple stressors and successfully fulfil their mission [10,11].…”
Section: Introductionmentioning
confidence: 99%